Monetary Policy Interaction within the EMS. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
A simple two-country stochastic model is used to analyze monetary policy interaction in a system of exchange rate bands such as the EMS, in the context of internationally-integrated financial markets. We consider the widely-acknowledged asymmetry of the system, as it pertains to member countries' use of monetary policy to offset shocks that impinge on their national incomes. Our results suggest, among other things, that tightening the exchange-rate bands would lead to more intervention by all members, even if formal responsibility for keeping exchange rates within the bands lay only with the peripheral countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet